DAMPAK PENERAPAN TARIF PAJAK EFEKTIF RATA-RATA (TER) TERHADAP PERHITUNGAN PAJAK PENGHASILAN PASAL 21 WAJIB PAJAK ORANG PRIBADI KARYAWAN TETAP PADA PT. ANUGRAH SEKAYU - Aryani, Farida; Romanda, Candra (Jurnal Ilmiah Akuntansi Rahmaniyah, 2024)
This descriptive research is aiming to analyze the impact of implementing TER on the calculation of PPh 21 WPOP for permanent employees at PT. Anugrah. The analysis technique is conducted by comparing calculation of PPh 21 WPOP based on tariffs 17 UU-HPP 7 of 2021 with TER based on PMK 168 of 2023. The secondary data is in the form of all income and calculation of PPh 21 for 32 WPOP permanent employees of PT. Anugrah. The results of this research show the calculation of PPh 21 WPOP a month for 32 permanent employees by applying TER is Rp 3,888,343, while the PPh calculation based on the article 17 rate is Rp 4,242,485. There is a difference in excess income tax deduction of Rp 354,142 a month. Implementation of TER can save taxes. It reduces tax burden and makes calculation process simpler and easier, so PMK regulation 168 of 2023 can reduce WPOP taxes, which is expected to increase awareness and voluntary compliance of WPOP. Apart from that, tax regulations have positive impact in increasing the amount of tax revenue. For this tax overpayment/withholding, request can be submitted for compensation.